2015
DOI: 10.1039/c5cy00343a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preparation method on the solid state properties and the deN2O performance of CuO–CeO2oxides

Abstract: The present work aims at investigating the catalytic decomposition of N 2 O over CuO-CeO 2 single or mixed oxides prepared by different synthesis routes, i.e., impregnation, precipitation and exotemplating. To gain insight into the particular role of CeO 2 as well as of CuO-CeO 2 interactions, three different types of materials are prepared and tested for N 2 O decomposition both in the absence and presence of excess O 2 : (i) bare CeO 2 prepared by precipitation and exotemplating, (ii) CuO/CeO 2 oxides synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 92 publications
1
55
1
Order By: Relevance
“…In all cases, the main contributions have been ascribed to the presence of Ce 4+ species, although Ce 3+ species have been also detected, as the Ce 3+ /Ce 4+ ratio indicates (Table 3). These data can be related to the H 2 -consumed/H 2 -theoretical ratio (Table 2) due to the formation of smaller particles that lead to a higher proportion of surface area, which is more easily reducible [61]. However, these data are not in accordance with the Raman spectra, so it is expected that Ce species tend to undergo a photoreduction process despite the short irradiation time.…”
Section: Characterisation Of the Catalystscontrasting
confidence: 46%
“…In all cases, the main contributions have been ascribed to the presence of Ce 4+ species, although Ce 3+ species have been also detected, as the Ce 3+ /Ce 4+ ratio indicates (Table 3). These data can be related to the H 2 -consumed/H 2 -theoretical ratio (Table 2) due to the formation of smaller particles that lead to a higher proportion of surface area, which is more easily reducible [61]. However, these data are not in accordance with the Raman spectra, so it is expected that Ce species tend to undergo a photoreduction process despite the short irradiation time.…”
Section: Characterisation Of the Catalystscontrasting
confidence: 46%
“…Major peaks of Cu 2p 3/2 at 932.5 eV and Cu 2p 1/2 at 952.3 eV confirmed the existed of metallic copper202136, demonstrated the successful photoreduction of CuCl 2 . Meanwhile, the peaks of Cu 2p 3/2 at 934.6 eV and Cu 2p 1/2 at 954.6 eV in combination with the satellite peaks at 941.5 eV and 944.3 eV are typical characteristics of CuO203637, implying the uniformly surface oxidation of Cu nanoclusters exposed in air under ambient conditions. These results are consistent with the TEM characterization.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated results are listed in Table 1 species in pure CeO 2 mainly points out that the sample has not been fully oxidized, rather than represents for the formation of oxygen vacancies [22]). This phenomenon could be ascribed to the synergistic interaction between Gd and Ce oxides (as mentioned in the section of XRD characterization), which leads to the facilitation of redox cycles between Ce 3+ and Ce 4+ [32]. The O1s XP core level spectra of the RE doped and pure ceria catalysts are demonstrated in Fig.…”
Section: Xps H 2 -Tpr and Osc Measurementsmentioning
confidence: 95%
“…More importantly, it is reported that the existence of Ce 3+ in doped ceria based catalysts is generally associated with the formation of oxygen vacancies, and higher concentration of Ce 3+ implies larger amounts of oxygen vacancies [31]. The relative Ce 3+ concentration can be determined by the ratio: Ce 3+ /(Ce 4+ + Ce 3+ ), where Ce 4+ and Ce 3+ represent the sums of the spectral peak areas related to the Ce 4+ and Ce 3+ , respectively [32]. The calculated results are listed in Table 1 species in pure CeO 2 mainly points out that the sample has not been fully oxidized, rather than represents for the formation of oxygen vacancies [22]).…”
Section: Xps H 2 -Tpr and Osc Measurementsmentioning
confidence: 98%